2013
DOI: 10.1111/1574-6968.12227
|View full text |Cite
|
Sign up to set email alerts
|

Effects on IS1transposition frequency of a mutation in theygjDgene involved in an essential tRNA modification inEscherichia coli

Abstract: The YgjD protein is essential for the synthesis of the universal tRNA modification, N(6) -threonylcarbamoyladenosine (t(6) A), which is necessary for the decoding of ANN codons. We isolated a suppressor (ygjDsup ) of the ygjD(ts) mutant by its permissive growth at high temperature in Escherichia coli. Resequencing of the ygjDsup mutant genome showed the presence of a complicated chromosome rearrangement, an inverse insertion of a large duplicated region (c. 450 kb) into a small deleted region. The temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…This suggested that these genes belonged to a complex regulatory network (Msadek, ), but the rstA suppression phenotype has never been really explained. Overexpression of other genes such as rho , encoding a transcription terminator, or dnaG , encoding DNA primase, have also been reported to suppress the essentiality phenotype caused by depletion of the t 6 A synthesis enzymes (Hashimoto et al ., 2011; 2013; Bergmiller et al ., ), but it is unknown if t 6 A is absent from tRNA isolated from these suppressor strains. Lack of t 6 A‐modificed tRNA in these strains would compromise the development of antibacterials targeting the enzymes of t 6 A machinery, as resistant clones could be selected at a high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that these genes belonged to a complex regulatory network (Msadek, ), but the rstA suppression phenotype has never been really explained. Overexpression of other genes such as rho , encoding a transcription terminator, or dnaG , encoding DNA primase, have also been reported to suppress the essentiality phenotype caused by depletion of the t 6 A synthesis enzymes (Hashimoto et al ., 2011; 2013; Bergmiller et al ., ), but it is unknown if t 6 A is absent from tRNA isolated from these suppressor strains. Lack of t 6 A‐modificed tRNA in these strains would compromise the development of antibacterials targeting the enzymes of t 6 A machinery, as resistant clones could be selected at a high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Mitomycin C and gamma-irradiation resulted in IS transposition in D. radiodurans [48][49][50][51]. When the translation error rate was enhanced by mutation of ygjD and rpsL encoding the universal tRNA and rRNA modifying proteins, respectively, or under high glucose growth conditions, active transposition of an IS1 family member was found in Escherichia coli [47,52]. Additionally, nutritional stress and host factors have been implicated in the transposition of ISs and TEs [53,54].…”
Section: Discussionmentioning
confidence: 99%